White pupae phenotype of tephritids is caused by parallel mutations of a MFS transporter - Ward, Christopher M; Aumann, Roswitha A; Whitehead, Mark A; Nikolouli, Katerina; Leveque, Gary; Gouvi, Georgia; Fung, Elisabeth; Reiling, Sarah J; Djambazian, Haig; Hughes, Margaret A; Whiteford, Sam; Caceres-Barrios, Carlos; et al. (Nature communications, 2021)
Mass releases of sterilized male insects, in the frame of sterile insect technique programs, have helped suppress insect pest populations since the 1950s. In the major horticultural pests Bactrocera dorsalis, Ceratitis capitata, and Zeugodacus cucurbitae, a key phenotype white pupae (wp) has been used for decades to selectively remove females before releases, yet the gene responsible remained unknown. Here, we use classical and modern genetic approaches to identify and functionally characterize causal wp- mutations in these distantly related fruit fly species. We find that the wp phenotype is produced by parallel mutations in a single, conserved gene. CRISPR/Cas9-mediated knockout of the wp gene leads to the rapid generation of white pupae strains in C. capitata and B. tryoni. The conserved phenotype and independent nature of wp- mutations suggest this technique can provide a generic approach to produce sexing strains in other major medical and agricultural insect pests.
Keywords: Genome, Insect; Reproduction; CRISPR-Cas systémy; rozmnožování; sekvence nukleotidů; hmyzí proteiny; Female; mutace; genom hmyzu; biologická kontrola škůdců; fertilita; Phenotype; zvířata; kukla; CRISPR-Cas Systems; Amino Acid Sequence; ženské pohlaví; Base Sequence; Male; Fertility; fenotyp; Pest Control, Biological; Ceratitis capitata; Animals; Mutation; Pupa; mužské pohlaví; Insect Proteins; Tephritidae; sekvence aminokyselin